(untitled) (Progress Annals: Journal of Progressive Research, 2024)
This article is one of the actual problems of the present time, textbooks and educational-methodical manuals and other educational-methodical complexes are of great importance in improving the quality of education. It is focused on the possibilities of using electronic literature in the educational process for young people and the formation of the scientific outlook of young people.